2018
DOI: 10.1136/bmjqs-2017-007778
|View full text |Cite
|
Sign up to set email alerts
|

Implementing bedside rounds to improve patient-centred outcomes: a systematic review

Abstract: BR have been implemented in a variety of hospital settings, often 'bundled' with cointerventions. However, BR have demonstrated limited effect on patient-centred outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 60 publications
0
31
0
Order By: Relevance
“…Reviews of the impact of person-centred care on falls in acute care settings also reported that some but not all studies identified significant improvements in falls rates (Avanecean et al, 2017, Klancnik Gruden et al, 2020. There was no evidence of impact of person-centred care on infection rates, although very few studies explored this relationship (Klancnik Gruden et al, 2020, Ratelle et al, 2019, Brownie and Nancarrow, 2013. Two reviews identified some positive effect of person-centred initiatives on reducing use of potentially inappropriate medications, including benzodiazepines (Mokhar et al, 2018) and anti-psychotic medication for older residents in care homes (Fossey et al, 2014).…”
Section: Safety Outcomes and Key Resultsmentioning
confidence: 99%
“…Reviews of the impact of person-centred care on falls in acute care settings also reported that some but not all studies identified significant improvements in falls rates (Avanecean et al, 2017, Klancnik Gruden et al, 2020. There was no evidence of impact of person-centred care on infection rates, although very few studies explored this relationship (Klancnik Gruden et al, 2020, Ratelle et al, 2019, Brownie and Nancarrow, 2013. Two reviews identified some positive effect of person-centred initiatives on reducing use of potentially inappropriate medications, including benzodiazepines (Mokhar et al, 2018) and anti-psychotic medication for older residents in care homes (Fossey et al, 2014).…”
Section: Safety Outcomes and Key Resultsmentioning
confidence: 99%
“…Previous reviews have investigated the efficacy of specific aspects of PFE on patient safety (McDonald, Bryce, & Graber, ; Ratelle et al, ; Ward & Armitage, ) and the present review represents the next step to obtaining a comprehensive picture of the impact of PFE on patient safety. However, the available evidence does not fully cover all factors related to both input (PFE) and output (patient safety).…”
Section: Discussionmentioning
confidence: 99%
“…Although our intervention sought to reshape ICU rounds for the benefit of fellows and residents, we also witnessed an increase in the fellow-nurse and fellow-patient interactions. We did not measure whether these interactions with stakeholders affected their perceptions of rounds, but an immense body of literature supports nurses’, patients’, and families’ receptiveness to rounding models that incorporate bedside teaching and patient-centered care ( 15 , 16 ), including in ICUs ( 17 , 18 ). Thus, increasing bedside interactions between fellows and these stakeholders likely has positive effects on communication among stakeholders ( 15 17 ) without sacrificing the educational value of rounds ( 18 ).…”
Section: Discussionmentioning
confidence: 99%